Increasing The Sales Productivity Of 'Tette Chips' During the Time of The Covid-19 Pandemic, Through Digital Marketing: Case study of Blumbungan Village, Larangan Pamekasan District - Akhmad Fawaid (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2022)
The Covid-19 pandemic that hit the world and Indonesia, had an impact on the decline in the income of the “ceripik tette” sellers in Blumbungan Village, Larangan District, Pamekasan. Conventional marketing that is carried out by "ceripik tette" sellers by selling directly in traditional markets and peddling to residents' homes is not possible during the pandemic. The purpose of this research is to find a solution to the problem faced by the "crepik tette" seller by changing the sales pattern with digital marketing. The research method used in this research is descriptive qualitative method. The benefits of this research, namely to provide benefits and convenience in doing business digitally to the public, even though they were in the covid-19 pandemic period and increased understanding of sellers about the existence of the internet. The results of this study, namely the increasing selling power of "tette crepik" with digital marketing.